Biogenic synthesis of silver nanoparticles via indigenous Anigozanthos manglesii, (red and green kangaroo paw) leaf extract and its potential antibacterial activity - Shah, Monaliben; Poinern, Gérrard Eddy Jai; Fawcett, Derek (International Journal of Research in Medical Sciences, 2017)
Background: Metallic silver nanoparticles with antibacterial properties were biosynthesised for the first time using an indigenous Australian plant Anigozanthos manglesii. Methods: A practical, straight-forward and eco-friendly technique used the Anigozanthos manglesii leaf extract, which acted as both reducing and capping agents to create stable silver nanoparticles. The antibacterial activities of the nanoparticles were investigated using the Kirby-Bauer sensitivity method. Results: Characterisation revealed the nanoparticles ranged in size from 50 nm up to 150 nm, and their morphologies included cubes, triangular plates and hexagonal plates. Antibacterial studies revealed Deinococcus was sensitive and susceptible to the biosynthesised nanoparticles. Escherichia coli and Staphylococcus Epidermis strains were also found to be less susceptible to the silver nanoparticles. Conclusions: The present study has shown that silver nanoparticles biosynthesised using Anigozanthos manglesii leaf extracts have antibacterial activity against Deinococcus, Escherichia coli and Staphylococcus Epidermis bacterial strains.